Inovasi Pelayanan Administrasi Kependudukan SIPINTER Online di Desa Tegal Harum Kota Denpasar - Ruben Zefanya Marselinus; Komang Adi Sastra Wijaya; Juwita Pratiwi Lukman (International Forum of Researchers and Lecturers, 2025)
The SIPINTER Online innovation in Tegal Harum Village is a form of digital service development aimed at improving public service efficiency and expanding service coverage. However, in its implementation, SIPINTER Online has not yet provided optimal benefits. This is due to the low number of community members in Tegal Harum Village who utilize the SIPINTER Online innovation. This study aims to identify the factors contributing to the low usage of SIPINTER Online in the village. The research employs a qualitative method with a descriptive approach. The analysis uses Rogers’ theory of innovation attributes, which includes relative advantage, compatibility, complexity, trialability, and observability. The findings show that the dissemination of information about SIPINTER Online is still lacking, resulting in limited public awareness. Moreover, hesitation in using technology and the community’s preference for conventional services are contributing factors to the low adoption rate. Therefore, SIPINTER Online has not yet delivered maximum benefits due to its limited reach. The recommendations include strengthening compatibility through sociocultural integration, reducing perceived complexity through education, increasing trialability through guided trials and direct outreach, and establishing feedback and continuous improvement mechanisms.